The Political Economy of Commercial Associations: Building the National Board of Trade, 1840–1868. Issue 4 (8th January 2015) - Davis, Cory
<x content-type="archive" xml:space="preserve">Abstract</x> This article argues that, in the mid-nineteenth century, the American merchant community created local commercial organizations to propagate a vision of economic development based on republican ideals. As part of a "business revolution, " these organizations attempted to balance competition and cooperation in order to promote and direct the expansion of national markets and commercial activity throughout the country. Faced with the crisis of divergent sectional political economies and committed to the belief that businessmen needed a stronger political voice, merchant groups banded together to form the National Board of Trade, an association devoted to creating a unified commercial interest and shaping national economic policies.